Status of the Saker Falcon in Hungary between 1980 and 2022 - Janos Bagyura; Tamas Szitta; Laszlo Haraszthy; Matyas Prommer; Marton Horvath (Пернатые хищники и их охрана)
There is limited data available about the status of the Saker Falcon (Falco cherrug) in Hungary before 1980. According to available sources, the species was a regular breeder in several habitat types, but was not common in the late 19th and early 20th centuries. The population decreased significantly through the 20th century falling to fewer than 50 pairs after World War II. The main reasons for the population decrease were DDT and widespread persecution (poisoning and shooting) of raptors by hunters. The species had reached the brink of extinction in Hungary by the 1970s. The Hungarian population of Saker Falcon is closely monitored and protected by MME BirdLife Hungary and the Hungarian National Park directorates’ ranger service over the last forty years.